Pengaruh Psikologis Mahasiswa Terhadap Penggunaan AI: Scoping Review - Najwa, Aina (Maliki Interdisciplinary Journal, 2025)
The phenomenon that is the background of this research is the increasing adoption of AI in various fields, including education, and the differences in psychological responses among students regarding the acceptance and use of this technology. The purpose of this study is to identify and analyze various psychological factors that influence students’ attitudes and behaviors towards AI. The method used is a scoping review, where relevant literature is identified, selected, and systematically analyzed to provide a comprehensive picture of this topic. The results of the study indicate that factors such as technology anxiety, self-efficacy, perceived benefits, and previous experience with digital technology play a significant role in influencing students’ attitudes towards the use of AI. Students who have high levels of self-efficacy and perceptions of the benefits of AI tend to be more accepting and using this technology. Conversely, technology anxiety and previous negative experiences can be inhibitors. These findings emphasize the importance of a more holistic approach to integrating AI into educational environments, taking into account psychological aspects to increase acceptance and effectiveness of its use.